2013
DOI: 10.1007/s10815-013-0104-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variations within and between incubators—a prospective, observational study

Abstract: Purpose To determine if there is a temperature variation within and between incubators. Methods This prospective, experimental trial with external controls was performed at an Assisted Reproductive Technology laboratory in a tertiary-care, university hospital. Temperature values were taken at various locations within and between incubators. Results Even though they were both set to 37.0°C, the same make and model incubators had significantly different internal temperatures. Temperatures differed significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…A preliminary report indicated slight temperature variations when culture dishes were placed in various locations within a large-box water-jacketed incubator, with measurements of 36.97°C, 37.17°C and 37.23°C (Stoddart et al, 2003). Similar findings were also recently reported between two large-box incubator, where minor (0.07-0.17°C), but significant temperature differences were identified between shelves and between incubators (Walker et al, 2013). Whether such minor fluctuations have an impact is unknown, but independent temperature measurement between shelves on box-type units, between individual culture chambers or across warmed surfaces of various benchtop/topload unit configurations can provide insight into temperature accuracy, as well as possible variation that could impact gamete and embryo development and function.…”
Section: Temperaturesupporting
confidence: 76%
“…A preliminary report indicated slight temperature variations when culture dishes were placed in various locations within a large-box water-jacketed incubator, with measurements of 36.97°C, 37.17°C and 37.23°C (Stoddart et al, 2003). Similar findings were also recently reported between two large-box incubator, where minor (0.07-0.17°C), but significant temperature differences were identified between shelves and between incubators (Walker et al, 2013). Whether such minor fluctuations have an impact is unknown, but independent temperature measurement between shelves on box-type units, between individual culture chambers or across warmed surfaces of various benchtop/topload unit configurations can provide insight into temperature accuracy, as well as possible variation that could impact gamete and embryo development and function.…”
Section: Temperaturesupporting
confidence: 76%
“…Temperature sensitivity of preimplantation embryos is less well studied. While one study on incubator performance reported an increased pregnancy rate from incubators with a temperature of 36.96 ± 0.13°C compared with those with a temperature of 37.03 ± 0.13°C (Higdon et al, 2008), another that reported slight temperature gradients of up to 0.3°C between shelves in culture incubators found no significant impact on clinical outcomes (Walker et al, 2013). Of importance, accuracy of these minor temperature variances is less than the uncertainty of measurement of most thermometers.…”
Section: Temperature In the Ivf Laboratorymentioning
confidence: 99%
“…vicina (22), P. casei (23) and L. sericata (19), are more likely to provide problems in PMI estimation using ADD following refrigeration as their continued development may skew the PMI estimation if refrigerator temperatures fluctuate too greatly. Walker et al (24), recommends that the temperatures within refrigerators must be evaluated and if significant variations are present appropriate measures must be taken in the analysis of insects taken from human remains. This is an area for concern though, as it requires death-scene technicians and/or mortuary staff to ensure they are recording these temperatures and that the temperatures are not merely assumed to be that of the set temperature of the refrigerator.…”
Section: Discussionmentioning
confidence: 99%